Hydrodeoxygenation of dibenzofuran to bicyclic hydrocarbons using bimetallic Cu-Ni catalysts supported on metal oxides - Ambursa, M.M. (Elsevier, 2016)
This work reports hydrodeoxygenation of dibenzofuran into bicyclic hydrocarbons over Cu-Ni catalysts supported on TiO2, ZrO2 and CeO2. The supported Cu-Ni catalysts were synthesized using a wet-impregnation method and calcined and reduced at 500 °C in accordance with TGA, DSC, and H2-TPR results. The catalyst properties were systematically examined using Raman, XRD, SEM, EDX and XPS techniques. XRD and Raman studies reveal the existence of cubic phase CeO2, monoclinic ZrO2, anatase TiO2, and cubic NiO in the synthesized catalysts. H2-TPR results show the simultaneous reduction of Cu2+ to Cu0 and Ni2+ to Ni0, forming bimetallic Cu-Ni alloy. Among the supports, a high dispersion of Cu-Ni particles was found on the CeO2 support, as evidenced by SEM studies. The reduced catalysts were investigated for hydrodeoxygenation of dibenzofuran at 250, 260 and 270 °C at 100 H2 bar for 6 h. The results show that the conversion of dibenzofuran increases with the increase of temperature: at 250 and 260 °C CuNi/TiO2 catalyst showed higher dibenzofuran conversions of 96% and 99% than the NiCu/CeO2 catalyst with relatively low conversions of 89% and 98%, respectively. In contrast, low conversions of 63% and 68% were found for the CuNi/ZrO2 catalyst under identical reaction conditions. In the case of selectivity to hydrocarbons, NiCu/TiO2 catalyst showed excellent selectivity to bicyclohexyl compared with that of NiCu/CeO2 and NiCu/ZrO2 catalysts at 260 °C. However, in terms of selectivity to bicyclohexyl-1-ene, NiCu/CeO2 catalyst showed the highest selectivity at 250 °C, while NiCu/ZrO2 catalyst exhibited the highest selectivity at 260 and 270 °C.